Admitting a bad influence: contracting the public service - Gibson, Ed. (2004)
Emulation of the private sector is a longstanding controversy in public administration, but could it constitute a bad influence, of the kind that parents seek to guard against by scrutinizing their children's peers? Effectiveness provides a perspective on how helpful or harmful private sector influence has been for the public service. The practice of contracting-out under the A-76 process receives particular scrutiny relative to maintaining the effectiveness of public agencies. A second perspective on private sector influence examines, through the theoretical perspective of transaction-cost economics, the promise of cost savings that justified recent acceleration of contracting-out. The author, himself a government contractor, also bases his analysis on personal experience. - Reproduced.
Keywords: Public administration